Automated external defibrillator accessibility and overcoverage across the urban-rural gradient: a national cross-sectional geospatial analysis (Swiss Medical Weekly, 2026)
STUDY AIMS: Timely defibrillation is a critical determinant of survival in out-of-hospital cardiac arrests, yet public access to automated external defibrillators (AEDs) remains spatially and temporally uneven, particularly in decentralised health systems. This study aimed to quantify AED accessibility and spatial overcoverage across the urban–rural gradient using high-resolution geospatial data from Switzerland as a model system.METHODS: We conducted a national cross-sectional geospatial analysis using AED locations (n = 14,446) from Defikarte.ch (December 2024), hectare-level population grids from the Federal Statistical Office (2023) and the 9-category municipality typology. The primary outcome was AED accessibility, defined as the proportion of the population within a 300-metre retrieval buffer of a 24-hour-accessible AED. Secondary outcomes included population coverage gain, comparing current 24-hour AED access with a hypothetical scenario in which all AEDs are accessible 24-hours, and spatial overcoverage, defined as overlapping AED buffers, indicating redundancy. Population exposure quantified the share of residents within these zones. Differences across municipality types were tested using the chi-squared test, paired t-test and Kruskal–Wallis test with Dunn’s post-hoc comparison.RESULTS: Expanding all AEDs to 24-hour access significantly increased national coverage from 28.9% to 51.6% (t = 3.96, p